PENGARUH KUALITAS PELAYANAN TOUR LEADER TERHADAP LOYALITAS KONSUMEN PADA TRAVEL AGENT KENCANA WISATA TANJUNG DUREN JAKARTA - Cariena, Aggy; Eka Mahadewi, Ni Putu; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 3 No 2 (2015): Jurnal IPTA (December 2015), 2015)
The incre as ing amount of traveler is affecting  the tourism sector. T he role of tour leader is very significant to support the success of a tour . Tour leader as a front liner of the company is needed to maintain the consumer’s satisfaction which is also affect the consumer’s loyalty to the company. The purpose of this study is to find the effect of Service Quality toward Consumer’s loyalty from Kencana Wisata Tanjung Duren Jakarta. Data was collected by using the questionnaire . The types of data are quantitative which  obtained by calculating data from the questionnaire . The method of sampling used purposive with the determination of respondents .The data method analyzed used double regression analysis techniques , double correlation , analysis of determination , T - test and F -test with significant level of 5 percent .Assisted by using data processing program SPSS ( statistical package for social science ) 15. The research result indicates that service quality of tour leader and consumer’s loyalty has a positive relation partially. Simultaneously,indicates that tangible (X 1 ), empathy (X 2 ), reliability (X 3 ), responsiveness (X 4 ) and assurance (X 5 ) loyalty  (Y) with value 0,834  which means significantly affecting consumer’s at travel agent Kencana Wisata Tanjung Duren Jakarta. The writer’s  suggestion is Kencana Wisata management should give special attention to maintain the honest behavior and make the tour leader more trustable to boost the consumer’s satisfactian which by the end can affect the consumer’s loyalty to the company.
Keywords: Service Quality, Tour Leader, Consumer’s Loyalty, Travel Agent